VGG-16 Transfer Learning for Accurate Classification of Three Local Durian Varieties Using Leaf Morphology Images - Nuqqy Zahhar, Ahmad Haikal; Mas Diyasa, I Gede Susrama; Prami Swari, Made Hanindya (Informatika, Universitas Jenderal Soedirman, 2026)
Durian (Durio zibethinus Murr), recognized as the